2021
DOI: 10.3390/en14175542
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CO2 Flooding on the Wettability Evolution of Sand-Stone

Abstract: Wettability is one of the main parameters controlling CO2 injectivity and the movement of CO2 plume during geological CO2 sequestration. Despite significant research efforts, there is still a high uncertainty associated with the wettability of CO2/brine/rock systems and how they evolve with CO2 exposure. This study, therefore, aims to measure the contact angle of sandstone samples with varying clay content before and after laboratory core flooding at different reservoir pressures, of 10 MPa and 15 MPa, and a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…However, the mineral content did not change much before and after the reaction. Other mineral-related reactions were not verified in this report, as shown in Table 5 [65].…”
Section: Sandstonementioning
confidence: 58%
See 2 more Smart Citations
“…However, the mineral content did not change much before and after the reaction. Other mineral-related reactions were not verified in this report, as shown in Table 5 [65].…”
Section: Sandstonementioning
confidence: 58%
“…Brine 2 was composed of 5 wt% NaCl and 1 wt% KCl. In contrast, after the sandstone flooded by brine 1 at (10 MPa, 15 MPa) and 50 • C for 7 days, it was found that the advancing/receding angle (θ A , θ R ) in the system of CO 2 -brine 2-sandstone was greater and the sandstone even became CO 2 -wet at a higher pressure (15 MPa) at 50 • C [65], as shown in Table 5.…”
Section: Sandstonementioning
confidence: 94%
See 1 more Smart Citation
“…Sole reliance on structural trapping could be risky as even a meticulous assessment of caprock integrity can miss some structural flaw. However, by virtue of the non‐wetting nature of CO 2 in the reservoir pore surfaces, capillary pressure among phases of formation fluids instigates saturation hysteresis that traps CO 2 as residual gas 17–20 . The effects of hysteresis are very prominent in processes that involve strong flow reversals, for instance, in a WAG operation 21 .…”
Section: Trapping Mechanismsmentioning
confidence: 99%
“…However, by virtue of the non-wetting nature of CO 2 in the reservoir pore surfaces, capillary pressure among phases of formation fluids instigates saturation hysteresis that traps CO 2 as residual gas. [17][18][19][20] The effects of hysteresis are very prominent in processes that involve strong flow reversals, for instance, in a WAG operation. 21 Literature has provided several residual gas trapping models that predict the hysteresis effect of CO 2 .…”
Section: Trapping Mechanismsmentioning
confidence: 99%